Modeling simple alcohols in two dimensions - Hribar, Barbara (Acta chimica slovenica, 2006)
The alcohol-water mixtures were studied within a two-dimensional model. The MB model was used for modeling water and alcohol molecules were modeled as non-flexible chains consisting of two-dimensional Lennard-Jones disks with the first disk having two hydrogen-bonding arms. The model was explored using NPT Monte Carlo computer simulation. The results were compared with the experimental thermodynamic properties of methanol-water mixtures. The qualitative agreement was obtained for the excess volume of mixing, but due tothe surface-volume effects not properly captured by two dimensional models, the excess enthalpy of mixing cannot be represented correctly by this model. Further, we studied the transfer of a single alcohol molecule into water, focusing on the trends exhibited by the methanol, ethanol, propanol, n-butanolseries. While small alcohol molecules show the correct trend the flexibility of the alcohol molecules should be taken into account to improve the agreement for higher alcohols.
Keywords: alkoholi; dimenzioniranje; fizikalna kemija; metoda Monte Carlo; modeli; Monte Carlo method; računalniške simulacije; raztopine; termodinamika